FINCA – a conceptual framework to improve interprofessional collaboration in health education and care - Witti, Matthias J.; Zottmann, Jan M.; Wershofen, Birgit; Thistlethwaite, Jill E.; Fischer, Frank; Fischer, Martin R. (Frontiers in Medicine, 2023)
The health care system in Germany and in many other countries is facing fundamental challenges due to demographic change, which require new integrated care concepts and a revision of the collaboration between health care professions in everyday clinical practice.Internationally, several competency framework models have been proposed, but a framework that explicitly conceptualizes collaborative activities to improve interprofessional problemsolving competency in health care is still missing. Such a framework should define contextual, person-related, process-related, and outcome-related variables relevant to interprofessional problem solving in health care. Against this background, we present a conceptual framework to improve interprofessional collaboration in health education and care (FINCA) developed with scientific consideration of empirical data and various theoretical references. FINCA reflects an interprofessional learning and interaction process involving two persons from different health care professions and with different individual learning prerequisites. These two initially identify a problem that is likely to require interprofessional collaboration at some point. FINCA acknowledges the context of interprofessional learning, teaching, and working as well as its action-modifying context factors. We follow the reasoning that individual learning prerequisites interact with the teaching context during learning activities. At the heart of FINCA are observable collaborative activities (information sharing and grounding; negotiating; regulating; executing interprofessional activities; maintaining communication) that can be used to assess individuals' cognitive and social skills. Eventually, the framework envisages an assessment of the outcomes of interprofessional education and collaboration.The proposed conceptual framework provides the basis for analysis and empirical testing of the components and variables it describes and their interactions across studies, educational interventions, and action-modifying contexts. FINCA further provides the basis for fostering the teaching and learning of interprofessional problem-solving skills in various health care settings. It can support faculty and curriculum developers to systematize the implementation and improvement of interprofessional teaching and learning opportunities. From a practical perspective, FINCA can help to better align curricula for different health professions in the future. In principle, we also see potential for transferability of the framework to other areas where different professions collaborate.